Components of Physical Abilities on a Fast Climb 18 Peaks 12 Days at Altitudes Above 3000 MDPL - Miftachul Chamim; Nurlan Kusmaedi; Mulyana Mulyana; Asep Ridwan Kurniawan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
This study aims to determine the dominant and supporting factors regarding the components of the PAMOR FPOK UPI mountain climbers' physical abilities on fast climbing. This research method uses the expost-facto method. Data collection techniques using physical abilities instruments as many as 7 respondents. The sampling method uses non-probability with purposive sampling technique. Data analysis used confirmatory factor analysis with the help of SPSS 23 software for windows. The results of this study show that the physical abilities of mountain climbers consist of 15 components, namely Circulatory respiratory endurance, General strength, Right thigh circumference, Left thigh circumference, Speed & power, Elastic strength, Body weight, BMI, Percent body fat, and supporting components including are Agility, Balance, Anxiety, Circumference of the upper right hand, Circumference of the upper left hand. The factors that have the highest contribution to the physical abilities of PAMOR FPOK UPI mountain climbers are Muscular endurance, agility, endurance cardiorespiratory fitness, muscular strength and power percentage 36.452%.